immunomodulation of echinococcosis with estrogen progesterone and HCGL - AL-Kaisy, ghassan H. J; Mohammed, khalil I.; AL-Jewari, Majid M.M. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Echinococcosis is a zoonotic disease with high incidence.